1990
DOI: 10.1007/bf00182642
|View full text |Cite
|
Sign up to set email alerts
|

Long term evaluation of high tibial valgus osteotomy

Abstract: SUMMARYWe present a long term evaluation of 100 high valgus tibial osteotomies with a mean follow up of 11 years. Knees with slight or moderate osteoarthritis had the best results. Slight overcorrection was beneficial, but gross overcorrection was not. There were few complications and the overall long term results were good. RÉSUMÉNous présentons une évaluation à long terme de cent ostéotomies de valgisation de l'extrémité supérieure du tibia, avec un recul moyen de 11 ans. Ce sont les genoux atteints d'arthro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0
3

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 14 publications
2
21
0
3
Order By: Relevance
“…Long-term results of HTO show a progressive deterioration, although there is a discrepancy between good clinical function and a poor radiological appearance [7,15,22,24,25]. The amount of correction remains a matter of controversy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term results of HTO show a progressive deterioration, although there is a discrepancy between good clinical function and a poor radiological appearance [7,15,22,24,25]. The amount of correction remains a matter of controversy.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of correction remains a matter of controversy. Overcorrection is recommended by a number of investigators, who have observed better results [9,17,20,25] but, overcorrection may create cosmetic problems or difficulties with future revisions. Average loss of correction in our study was 3.2°and at 10-15 years 3.7°.…”
Section: Discussionmentioning
confidence: 99%
“…High tibial osteotomy typically results in pain relief and improved knee function in 80-90 % of patients [3,10,21]; however, osteoarthritis progression often leads to deterioration of results with the passage of time [13,14,18,22,24]. When symptomatic progression occurs, total knee arthroplasty (TKA) is frequently performed.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have shown that the long-term result depends on the degree of correction achieved after bone healing. A slight over-correction gives the best shortand long-term results (Kettelkamp et al 1976, Valenti et al 1990, Coventry et al 1993. Various techniques for fixation of the osteotomy had been described, including plaster fixation, orthoses, combinations of staples, plates and external fixation (Ivarsson and Larsson 1989, Koshino et al 1989, Miniaci et al 1989, Yasuda et al 1992, Zuegel et al 1996.…”
mentioning
confidence: 99%